ANALISIS PRODUK BINAR GO MENGGUNAKAN PRIORITIZATION MATRIKS EISENHOWER DAN MODEL KANO - Renisa Nur Kamelia Putri; Dian Permata Sari; Rian Andrian (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
Edutech startups are currently experiencing rapid development. This is because the need for Indonesian digital skilled workers reaches 9 million people in 2030. One way to be able to print digital skilled workers according to industry needs is by building an edutech startup. One of the edutech startups whose goal is to produce quality young people is Binar Academy. Various courses are provided with varying prices for subscriptions. The courses available at Binar Academy are Product Management, Frontend, Backend, Android Developer, UI/UX Designer and others. One of the newest products, Binar Go, provides interesting and flexible learning according to the needs of today's young generation. Product Binar Go has a huge opportunity to increase digital skilled workers. Especially for the younger generation who will enter the industrial world. This study uses a mixed method, namely quantitative and qualitative methods. In the survey, 55% said there were several obstacles when using the Binar Go android application that caused users to be less comfortable. To solve these problems and provide a higher quality learning experience, it is necessary to improve the product, one of which is by creating new features. Therefore, to complement the new features that do not exist in Binar Go, the researcher uses the prioritization of the Eisenhower Matrix and the Kano model in developing this product. The Eisenhower Matrix is ​​a feasible way of prioritizing a job and the Kano Model is a diagram that can help prioritize customer needs in more detail. By using the prioritization of the Eisenhower Matrix and the Kano model, it can help researchers to determine which features can be developed first to improve the quality of Binar Go's features.